Effect of diphenyliodonium hexafluorphosphate in the yellowing and properties of experimental resin cements - Kamila Menezes Guedes de Andrade; Caroline Mathias; Hugo Felipe do Vale; Flávio Henrique Baggio Aguiar; Giselle Maria Marchi (Universidade Estadual de Campinas, 2019)
Aim: The yellowing effect is undesirable and can occur in the dental restoration margins when light-cured resin cements containing camphorquinone as photoinitiator is used. This study aimed to evaluate the effect of diphenyliodonium hexafluorphosphate (DPI) in photoinitiator systems that contained different concentrations of camphorquinone (CQ) and dimethylamino ethyl benzoate (EDAB) on resin cements. Methods: A base (1:1) of bisphenol A diglycidyl methacrylate (BisGMA) and triethylene glycol dimethacrylate (TEGDMA) was obtained, and 60wt% of glass fillers was added. Eight formulations were obtained: RC1 (0.5mol% CQ / 1mol% EDAB), RC2 (0.5mol% CQ / 2mol% EDAB), RC3 (1mol% CQ / 1mol% EDAB), RC4 (1mol% CQ / 2mol% EDAB), and RC5 to RC8, which contained the same bases plus 0.5mol% DPI. Experimental resin cements were evaluated by the degree of conversion (DC), L*a*b* color analysis, water sorption (WS) and solubility (S), flexural strength, and Elastic Modulus. The data were analyzed by three-way ANOVA, Tukey's and Mann-Whitney tests (α = 0.05). Results: The combination of DPI and 0.5mol% CQ increased DC in RC6 and L* in RC5 without increasing the WS and a* b* values. CQ at 1mol% showed higher values of b* and lower values of a*, except for RC3. Groups with 2mol% EDAB showed higher DC. Conclusion: The addition of DPI reduces CQ, generating a decreased yellowing effect, while maintaining adequate properties in the resin cements, especially with 2mol% EDAB.